Future specialists in physical culture and sports cardiovascular system functional condition evaluation - V.I. Bobrytska; N.A. Beseda (Physical Education of Students)
Im: to investigate and evaluate future specialists in physical education and sports cardiovascular system adaptive potential. Research background and methods: 28 first (bachelor) level students aged 17-18, doing their degree in 017 “Physical Culture and Sports” (experimental group of 12 participants) and in 227 “Physical Therapy, Ergotherapy” (experimental group of 16 participants) from Poltava National Technical University specialism took part in the research. All the participants gave their written consent for participating in the research. Students’ cardiovascular adaptative potential was defined according to R. Baevsky methods. Results: 71.3% of boys and 69.2% of girls showed high level of the body functionality. Adaptive mechanisms tension features revealed 28.4% of female students and 26.6% of male students. Persons with failure of adaptation have not been found. Conclusions: The measurement of the cardiovascular system adaptative potential enables evaluating the level of students’ physical health condition. Consideration of students’ cardiovascular system adaptative potential indicators contributes to implementation of a differentiated approach to teaching Sports and Pedagogic disciplines. The above increases the quality of the occupational training of the future specialists in Physical Culture and Sports provided that their adaptive capacities are developed.